THE INHIBITORY AND BACTERICIDAL HEAT PROTECTION EQUIPMENT WORKING CYCLE OF THE USE OF PHENOLIC WASTEWATER - , С. В., В. И., Л. Д. (Municipal economy of cities. Series: «Economy science», 2013)
<span title="Приводятся результаты исследований по влиянию ингибиторов коррозии (фосфатно-силикатной смеси) и биоцидов на основе производных роданистоводородной кислоты на коррозионную активность оборотной воды цикла охлаждения коксового газа при использовании очищенных сточных фенольных вод.">The results of studies on the effect of corrosion inhibitors (phosphate - silicate mixture) and biocides based on derivatives rodanistovodorodnoy corrosive acid on the circulating water cooling cycle coke oven gas using treated waste water phenol . <span title="Использование ингибиторов и биоцидов значительно тормозит коррозионные процессы и это дает возможность значительно сократить использование чистой природной воды за счет утилизации фенольных вод коксохимических производств.">The use of inhibitors and biocides significantly inhibits corrosion processes and this makes it possible to significantly reduce the use of pure natural water by utilizing water phenolic coke production .